Calmodulin contributes to gating control in olfactory calcium-activated chloride channels - Kaneko, Hiroshi; Möhrlen, Frank; Frings, Stephan (The journal of general physiology, 2006)
In sensory neurons of the peripheral nervous system, receptor potentials can be amplified by depolarizing Cl currents. In mammalian olfactory sensory neurons (OSNs), this anion-based signal amplification results from the sequential activation of two distinct types of transduction channels: cAMP-gated Ca channels and Ca-activated Cl channels. The Cl current increases the initial receptor current about 10-fold and leads to the excitation of the neuron. Here we examine the activation mechanism of the Ca-dependent Cl channel. We focus on calmodulin, which is known to mediate Ca effects on various ion channels. We show that the cell line Odora, which is derived from OSN precursor cells in the rat olfactory epithelium, expresses Ca-activated Cl channels. Single-channel conductance, ion selectivity, voltage dependence, sensitivity to niflumic acid, and Ca sensitivity match between Odora channels and OSN channels. Transfection of Odora cells with CaM mutants reduces the Ca sensitivity of the Cl channels. This result points to the participation of calmodulin in the gating process of Ca-ativated Cl channels, and helps to understand how signal amplification works in the olfactory sensory cilia. Calmodulin was previously shown to mediate feedback inhibition of cAMP-synthesis and of the cAMP-gated Ca channels in OSNs. Our results suggest that calmodulin may also be instrumental in the generation of the excitatory Cl current. It appears to play a pivotal role in the peripheral signal processing of olfactory sensory information. Moreover, recent results from other peripheral neurons, as well as from smooth muscle cells, indicate that the calmodulin-controlled, anion-based signal amplification operates in various cell types where it converts Ca signals into membrane depolarization.